In vitro and in vivo targeting imaging of pancreatic cancer using a Fe3O4@SiO2 nanoprobe modified with anti-mesothelin antibody - Liu F; Le W; Mei T; Wang T; Chen L; Lei Y; Cui S; Chen B; Cui Z; Shao C (International Journal of Nanomedicine, 2016)
Fang Liu,1,* Wenjun Le,2,* Tianxiao Mei,2 Tiegong Wang,1 Luguang Chen,1 Yi Lei,1 Shaobin Cui,2 Bingdi Chen,2 Zheng Cui,2,3 Chengwei Shao1 1Radiology Department of Changhai Hospital, Second Military Medical University, 2Shanghai East Hospital, The Institute for Biomedical Engineering & Nano Science, Tongji University School of Medicine, Shanghai, People’s Republic of China; 3Department of Pathology, Wake Forest University School of Medicine, Winston-Salem, NC, USA *These authors contributed equally to this work Abstract: Pancreatic cancer is a highly malignant disease with a 5-year survival rate ,5% mainly due to lack of early diagnosis and effective therapy. In an effort to improve the early diagnostic rate of pancreatic cancer, a nanoprobe Fe3O4@SiO2 modified with anti-mesothelin antibody (A-MFS) was prepared to target cells and tumor tissues highly expressing mesothelin in vitro (human pancreatic cancer cell line SW1990) and in vivo (subcutaneously transplanted tumors) studies. The A-MFS probe was successfully prepared and was spherical and uniform with a hydrodynamic diameter between 110 and 130 nm. Cell Counting Kit-8 testing indicated that A-MFS was nontoxic in vitro and in vivo studies. The in vitro study showed that the A-MFS probe specifically targeted SW1990 cells with high mesothelin expression. The in vivo study was conducted in Siemens 3.0 T magnetic resonance imaging. The average T2-weighted signal values of the xenografts were 966.533±31.56 before injecting A-MFS and 691.133±56.84 before injecting saline solution. After injection of 0.1 mL A-MFS via nude mouse caudal vein for 2.5 hours, the average T2-weighted signal of the xenograft decreased by 342.533±42.6. The signal value decreased by -61.233±33.9 and -58.7±19.4 after injection of the saline and Fe3O4@SiO2. The decrease of tumor signal by A-MFS was much more significant than that by saline and Fe3O4@SiO2 (P<0.05). The results demonstrated the high stability and nontoxicity of A-MFS, which effectively targeted pancreatic cancer in vitro and in vivo. A-MFS is a promising agent for diagnosis of pancreatic cancer. Keywords: nanoprobe, mesothelin, Fe3O4@SiO2, pancreatic cancer, targeted imaging